Analysis of the Test Results of the Physical Condition Ability of Karate Athletes in West Java - Repany Julianty; Sagitarius; Geraldi Novian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Physical condition is one of the requirements needed in the effort to improve athletes' performance, and it can even be considered a basic necessity that cannot be postponed or negotiated. An athlete's physical condition is very important to achieve maximum performance. This study aims to analyze the general physical condition of karate athletes from West Java. The method of this research is a quantitative descriptive study with a typical descriptive design. The population in this study consists of 20 karate athletes from West Java aged 17-21 years. The sampling technique used is total sampling. The data collection technique uses a test instrument, which consists of 9 test items, namely the Sit and Reach Test, 20 M Sprint, Side Step Test, Medicine Ball Test, Vertical Jump Test, Push Up Test, Sit Up Test, Back Up Test, and Bleep Test. The data results using descriptive analysis with percentages based on categorization norms. The research shows that the physical condition of West Java karate athletes overall falls into the medium category, which is 81%, thus it can be concluded that the physical condition of West Java karate athletes is moderate. This research can serve as a guideline in evaluating the effectiveness of the training programs that have been implemented, allowing trainers to make improvements or adjustments to training programs in a more targeted manner.